Nilai Sosial dan Moralitas dalam Naskah Drama Janji Senja Karya Taofan Nalisaputra - Agung Nugroho (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2018)
The purpose of this study was to describe the social values and moral values of drama scripts. The drama manuscript used was titled Janji Senja by Taofan Nalisaputra. This study used descriptive qualitative method. The results of this study are a description of the study of social values and moral values of the drama drama Janji Senja by Taofan Nalisaputra. The results of the social value study that dominates the drama script Janji Senja by Taofan Nalisaputra namely the social value of self with others this is seen from the quote "The wife must obey the husband, rude speech affects other people's hearts, hatred that cuts the cord of blood in body, more concerned with others than his own mother ". This is clearly stated by the author in the manuscript. Whereas the moral values of the Janji Senja drama script by Taofan Nalisaputra cover several aspects including, in the form of behavior that is appropriate to decency, character, and morals. Based on these results, it is clear that the drama of the writing of Janji Senja by Taofan Nalisaputra is very strong in terms of social and moral values because the drama plays are directly related to daily life in the community.